ADAPTABILITY FAIR VALUE ACCOUNTING AT THE PUBLIC COMPANY IN INDONESIA - Dewi, Nurul Uswati (PEOPLE: International Journal of Social Sciences, 2015)
As a member of The Group of Twenty (G20 Forum), Indonesia have agreed to converge towards IFRS. Indonesian Institute of Accountants through the Accounting Standards Board announced that the Drafting international accounting standards (IFRS) came into force in Indonesia in 2012 as a whole. Gradual convergence towards IFRS have been conducted by the Indonesian Institute of Accountants with the revised Statement of Financial Accounting Standards (SFAS) adapted to IFRS so that companies going public are required to disclose financial information based on new or revised accounting principles that became effective in stages since 2008. This study did archiving accounting standards change over a period of 2008. The gradual change will have an impact on the qualitative characteristics of financial statements primarily on public companies. After the inventory accounting standard changes that occur, further research on the impact of changes in the reporting of public companies.This study aims to assess the feasibility and development of fair value accounting on the adaptation of public companies in this Indonesia. This study contributing picture adaptation of convergence Fair Value Accounting in Indonesia, which still continues to this day. The findings of this study provide new insights that can hamper international accounting convergence in developing countries.